A funeral in Mantova : a Rick Montoya Italian mystery - Wagner, David P. (Wagner, David P. Rick Montoya Italian mysteries., 2018)
"The body rolled off the planks and slipped into the water with barely a splash, quickly embraced by the steady current flowing toward the city of Mantova. It comes to rest against rocks overlooked by the grim ramparts of Castello di San Giorgio as the river Mincio flows on towards the Po and the Adriatic Sea...Rick Montoya, an American from New Mexico self-employed as a translator in Italy once again puts his linguistic skills to use for the local law in solving a crime." --adapted from Amazon.com.